USE OF FACEBOOK IN LEARNING VOCABULARY - Yudiati, Rini; Ach. Andiriyanto (Jurnal Cakrawala Ilmiah, 2024)
The objective of this research is to find out how the Facebook users of English students at Faculty of Health Science Wiraraja University increase their vocabulary in English. The Method of this research was A qualitative Descriptive and used Blachowicz and Fisher’s theory to answer research question. The research took 25 students as samples. The data were taken through questionnaire and open ended questions (interview). The result shows that according to most of student’s perception student can be active in developing their understanding of words and ways to learn vocabulary, students can personalize word learning, can immerse in words through Facebook, can build on multiple sources of information to learn words through repeated exposure by reading texts in Facebook. This result supports the four principles which stated by Blachowicz and Fisher (2000), and it gives positive effect to students